Modeling and Analysis of Identification Process Pertaining to Active Resistance of Induction Motor While Using Fuzzy Logic Observer - D. S. Odnolko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2012)
The paper presents method for joint identification of an active stator and rotor resistance of an induction motor on the basis of fuzzy logic controller. The problem is solved for the induction motor model presented in d–q coordinates and rotating with synchronous speed. The conditions required for the possibility of identification test have been determined in the paper. The paper has analyzed an effect of mutual inductance deviation, stator and rotor inductance deviations from their true values on the identification accuracy. The proposed method is applicable under conditions of steady state drive and runs in two phases. The simulation results indicate a high speed and accuracy of parameter identification.